Long-term mortality in patients with end-stage renal disease undergoing hemodialysis and peritoneal dialysis: a propensity score matching retrospective study - Pengjie Zhang; Liru Xun; Nan Bao; Ding Tong; Bin Duan; Du Peng (Renal Failure)
Background Hemodialysis (HD) and peritoneal dialysis (PD) are effective ways to treat end-stage renal disease (ERSD). This study aimed to investigate the differences in survival and the factors that influence it in patients with end-stage renal disease treated with HD or PD.Methods We retrospectively analyzed factors related to all-cause death with renal replacement therapy and compared the long-term mortality between HD and PD strategies in patients with ESRD who started HD or PD treatment in our renal HD center between January 1, 2008, and December 1, 2021.Results Overall, 1,319 patients were included, comprising 690 and 629 patients in the HD and PD groups, respectively, according to the inclusion criteria. After propensity matching, 922 patients remained, with 461 (50%) patients each in the two groups. There were no significant differences in the 1-, 2-, 3-, and 4-year mortality rates between the HD and PD groups (all p > .05). However, the 5- and 10-year mortality rates of the matched patients were 15.8%. 17.6% in the HD group and 21.0%. 27.3% in the PD group, respectively. The 5- and 10-year mortality rates were significantly lower in the HD group (all p < .05) as compared to the PD group. After matching, Kaplan–Meier curve analysis with log-rank test was performed, which showed a significant difference in the survival rates between the two groups (p = .001). Logistic multifactor regression analysis revealed that age, weight, hypertension, serum creatinine, and combined neoplasms influenced the survival rate of patients with ESRD (p < .05). In contrast, age, hypertension, parathyroid hormone (PTH), serum creatinine, and peripheral vascular diseases (PVD) influenced the survival rate of patients in the HD group (p < .05), and age and weight influenced the survival rate of patients in the PD group (p < .05).Conclusions This study found that long-term mortality rates were higher in the PD group than that in the HD group, indicating that HD may be superior to PD.